PENYULUHAN HUKUM TENTANG NARKOBA DI KELURAHAN PALABUSA KECAMATAN LEA-LEA - RIZKI MUSTIKA SUHARTONO; , WA ODE AL ZARLIANI; L. M RICARD ZELDI PUTRA; SAFRIN EDY; NILUH SUKMAYANTI (KRIDA CENDEKIA, 2021)
This community service aims to provide knowledge and understanding about drugs to the Palabusa village community. This community service is expected to be able to provide legal awareness to the public about the dangers of drugs from a legal and health perspective. The method used in the implementation of the activity is counseling, lectures and discussions. The results and discussion of this community service is legal counseling by involving students to practice providing legal counseling in front of the Palabusa sub-district community, Lea Lea sub-district. Legal education about drugs is very much needed for the generation of teenagers and parents. Given that people are very easy to be influenced by deviant behavior, including the abuse of illegal drugs.